FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS SUKAMAJU KABUPATEN LUWU UTARA - Silvah Silvah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Objective: To find out the factors related to the incidence of ARI in infants in Sukamaju Health Center, North Luwu Regency. Method: This type of research is used as an analytical survey with a cross sectional study approach, with the aim to find out the factors related to the incidence of ARI in infants in Sukamaju Health Center, North Luwu Regency. Population in the study. Results: Based on the SPSS test the calculated calculated value p = 0.022 (Age), p = 0.002 (Nutritional Status), and p = 0.023 (Immunization Status). Which means that all p values ??are smaller than the value of ? = 0.05. From the analysis it can be interpreted that Ho is accepted or there is a relationship between age, nutritional status, and immunization status with the incidence of ARI. Discussion: ARI stands for Acute Respiratory Tract Infection, was introduced in 1984 at the National ISPA workshop in Cipanas. This term is the equivalent of the English term Acute Respiratory Infection abbreviated as ARI. In the first National workshop there were two opinions. The first opinion chose the term ISPA (Acute Respiratory Infection) and the second opinion chose the term ISNA (Acute Respiratory Tract Infection). Conclusion: Based on the results of the study, the results showed that there was a relationship between age, nutritional status, and immunization status with the incidence of ARI in children under five who were treated at the Sukamaju Health Center in North Luwu Regency. Suggestion: Mothers of toddlers should know the importance of special attention to children aged 0–59 months. A toddler's mother is expected to be active to get information on growth and development of children aged 0 - 59 months. This information can be provided at posyandu, puskesmas, village and sub-district level meetings or in mosques